2013
DOI: 10.1042/cs20130152
|View full text |Cite
|
Sign up to set email alerts
|

CRAC channel inhibition produces greater anti-inflammatory effects than glucocorticoids in CD8 cells from COPD patients

Abstract: Background-There are increased numbers of pulmonary CD8 lymphocytes in COPD. Calcium-release activation calcium (CRAC) channels play a central role in lymphocyte activation though the regulation of the transcription factor nuclear factor of activated T cells (NFAT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…Exposure to Synta (10 μM) for 1.5 h did not induce any significant cytotoxicity compared to non-treated cells (data are not shown). Similarly, the cytotoxicity of Synta was previously assessed in CD8 cells and it was found that exposure to Synta (up to 10 μM) for 1 h did not result in increased cytotoxicity [33]. Taken together, these results suggest the important role of calcium in response to AgNP-mediated degranulation of mast cells…”
Section: Resultssupporting
confidence: 67%
“…Exposure to Synta (10 μM) for 1.5 h did not induce any significant cytotoxicity compared to non-treated cells (data are not shown). Similarly, the cytotoxicity of Synta was previously assessed in CD8 cells and it was found that exposure to Synta (up to 10 μM) for 1 h did not result in increased cytotoxicity [33]. Taken together, these results suggest the important role of calcium in response to AgNP-mediated degranulation of mast cells…”
Section: Resultssupporting
confidence: 67%
“…The anti-inflammatory effects of dexamethasone were similar in COPD patients and controls, both in PBMCs and CD8 cells from the blood and lung tissue. We have previously reported similar corticosteroid sensitivity in COPD and control CD8 cells from blood and lung tissue [ 15 ]. In contrast, stimulated bronchoalveolar lavage lymphocytes, containing CD4 and CD8 cells, show decreased corticosteroid sensitivity in COPD patients compared to controls [ 26 ].…”
Section: Discussionmentioning
confidence: 82%
“…Pulmonary CD8 cells were isolated as previously described [ 15 ]. Briefly, lung tissue was homogenised in a blender.…”
Section: Methodsmentioning
confidence: 99%
“…All compounds were effective in inhibiting both the proliferation (355) and the production of a wide range of cytokines, including IL-2, IFN-γ, TNF-α, and IL-17, by primary human T cells isolated from healthy controls (355) or from diseased tissues such as colonic lamina propria of patients with IBD (353) and lung of patients with chronic obstructive pulmonary disease (356). These findings are consistent with impaired cytokine expression in T cells from ORAI1/STIM1-deficient patients and mice (33, 125127, 155, 164, 168).…”
Section: Ion Channels As Drug Targets For Immunotherapymentioning
confidence: 99%